Umbilical Arterial Blood Gas and Perinatal Outcome in the Second Twin according to the Planned Mode of Delivery - Kwon, Ji Young (Ivyspring International Publisher, 2011)
Purpose: To compare umbilical arterial gas parameters in the second twin of twin pregnancies according to the mode of delivery Methods: We retrospectively analyzed the medical records of twin deliveries after 34 weeks of gestation for 3 years. Excluding the cases which underwent emergency cesarean delivery during trial of labor, a total of 79 twin gestations had umbilical arterial blood gas values available and were and divided into cesarean delivery group (N=40) and vaginal delivery group (N=39). The mean differences of umbilical arterial blood parameters and the Apgar score between the first and second twin in each pregnancy were compared according the mode of delivery. Results: The differences of umbilical arterial gas parameters between twin siblings showed no significant difference according to the mode of delivery. With regard to the 1 minute and 5 minute Apgar scores, the differences between twin siblings are significantly increased in vaginal delivery group compared to cesarean delivery group (p=0.048, and p=0.038, respectively). In comparing the 28 cases delivered vaginally with an inter-twin delivery interval < 10 minutes and 40 cases delivered by cesarean section, no significant differences were observed in the umbilical arterial gas parameters and Apgar scores. Conclusion: The inter-twin umbilical arterial blood gas parameters according to the mode of delivery showed no difference. For twin deliveries, it is relatively safe to plan for a vaginal delivery, but an effort should be made to reduce the inter-twin delivery interval time.